РАННЯЯ УЛЬТРАЗВУКОВАЯ ДИАГНОСТИКА СПЛЕНОМЕГАЛИИ У НОВОРОЖДЕННЫХ - Перепелица, Светлана Александровна; Сушкевич, Элина Сергеевна; Астахова, Екатерина Викторовна; Бахалова, Галина Евгеньевна (Медицина: теория и практика, 2020)